2019
DOI: 10.1002/psp.2236
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle migration from the Global South to the Global North: Individualism, social class, and freedom in a centre of “superdiversity”

Abstract: Lifestyle migration is a growing field of interest. Traditionally, research into lifestyle migration has focused on either "North to North" or "North to South" migration. This article analyses middle-class Brazilian migration to London together with examples from the lifestyle migration literature to argue that there are instances of movement from the Global South to the Global North, which should be classified as lifestyle migration according to how the term is used in the literature. This is important becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
(61 reference statements)
1
8
0
1
Order By: Relevance
“…It is a way for Brazilians to feel in power in relation to refugees, reaffirming the literature on asymmetric power relations in migration (Robins, 2019;Schurer & Day, 2019). Brazilians believe they are in a position of superiority over black refugees from the global South.…”
Section: Communication As a Gateway To Integration: From Good Intentions To Gross Racismsupporting
confidence: 52%
See 1 more Smart Citation
“…It is a way for Brazilians to feel in power in relation to refugees, reaffirming the literature on asymmetric power relations in migration (Robins, 2019;Schurer & Day, 2019). Brazilians believe they are in a position of superiority over black refugees from the global South.…”
Section: Communication As a Gateway To Integration: From Good Intentions To Gross Racismsupporting
confidence: 52%
“…Migration studies are marked by discussions on the hierarchy of power between developed and (under)developing countries referred to as north-south migration (Robins, 2019;Schurer & Day, 2019). However, this research focuses on the new migratory flow, South-South, which has brought new or even old implications to the world of work and in interpersonal relationships (Ratha & Shaw, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to trends found in Western countries, the relatively economically wealthy countries in the South have dealt with increased labor migration by both encouraging migrants and increasing restrictions on immigration (Nawyn, 2016). This increasing migration to wealthy countries in the South suggests that some differences in the motivation to migrate may be more about country-level factors, such as GDP, and group-level factors and circumstances, such as social class (Robins, 2019)-and less about a North-South difference.…”
Section: Commonalitiesmentioning
confidence: 75%
“…Recent research has also found that migrating for improved quality of life is not unique to the Global North and is a frequently cited motivation among middle-class people from the Global South (Robins, 2019). Increasing economic growth in the Global South has opened up new opportunities for skilled labor migration as well (Nawyn, 2016).…”
Section: Commonalitiesmentioning
confidence: 99%
“…However, there are great economic and power disparities, sustained by rules and bureaucracy that preserve the structural differences in wealth and power; this reveals a high degree of distrust towards individuals who do not belong to the same social groups (Coelho, 2019; Sobral et al, 2012). For instance, research conducted with Brazilian migrants in London found that practices of distancing from other Brazilians were commonly based on race and social class (Robins, 2019). Brazilian culture is also characterised by some level of insensitivity and a lack of consideration for other people's trajectories, which has historical roots in the slavery system that was common in the country until the 19th century (Holanda, 2012).…”
Section: Ethnic Entrepreneurship and Issues Of Trustmentioning
confidence: 99%